Cloning, expression and immunological evaluation of the Omp31 protein of Brucella melitensis and evaluation of its possible use for the diagnosis in bovine brucellosis - Rosales Rangel, Jose David (2018)
The serological diagnosis of brucellosis is carried out by the detection of antibodies generated against the liposaccharide «LPS» or bacterial extracts of whole cells by ELISA or agglutination tests. The objective of this study was to evaluate a recombinant protein that can be used in the serological diagnosis of bovine brucellosis. The Omp31 gene of Brucella melitensis 16M was chosen. The gene was cloned from DNA of B. melitensis; the expression of the Omp31r protein was performed in a prokaryotic expression system using the pET28a vector and purification by metal affinity chromatography (IMAC). An indirect ELISA was standardized using control sera from positive and negative bovines. The Omp31r protein reacted with the positive control sera and succeeded in discriminating against the negative sera. The sensitivity and specificity of the ELISA assay was 77.2% and 90.6%, respectively. This indirect ELISA system can be useful for the rapid diagnosis of large numbers of samples in the diagnosis of bovine brucellosis.